Indonesia’s Climate Diplomacy: Criticisms and Challenges of Biomass Co-firing Under JETP - Ade Arya Yunissa; Ali Maksum (Journal of Government and Politics (JGOP), 2026)
This study analyzes Indonesia’s climate diplomacy in developing biomass through coal co-firing policies as a strategy to achieve Net Zero Emissions (NZE) within the Just Energy Transition Partnership (JETP) framework. The research focus is directed at how Indonesia constructs its domestic energy transition narrative amid rising international criticism regarding the sustainability and effectiveness of biomass. Utilizing a qualitative method with a case study approach, data collection was conducted through a comprehensive literature review, analysis of government policy documents, international organization reports, and publications from global environmental institutions. Theoretically, this study applies the concepts of climate diplomacy and the just energy transition framework. The findings reveal a structural policy misalignment. Indonesia utilizes biomass co-firing as a diplomatic instrument to demonstrate its decarbonization commitment while maintaining national energy stability. However, this policy has drawn sharp global criticism for being perceived as a "false solution" that extends the lifespan of coal plants, risks driving deforestation through Energy Plantation Forest expansion, and weakens Indonesia's bargaining position, thereby stalling the disbursement of JETP grants. The novelty and research gap of this study lie in its shift from the technical-economic aspects of biomass to the political dimensions of international relations. This study fills a literature gap by mapping how the friction between domestic regulations and global green norms creates a deadlock in climate finance. The policy implications urge the Indonesian government to reconfigure its diplomatic strategy by tightening biomass sustainability standards and redirecting international funding toward pure renewable energy infrastructure.